2015
DOI: 10.1073/pnas.1419703112
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor interaction with COMPASS-like complex regulates histone H3K4 trimethylation for specific gene expression in plants

Abstract: Accumulation of unfolded or misfolded proteins causes endoplasmic reticulum (ER) stress, which activates a set of ER membraneassociated transcription factors for protein homeostasis regulation. Previous genome-wide chromatin immunoprecipitation analysis shows a strong correlation between histone H3K4 trimethylation (H3K4me3) and active gene expression. However, how the histone modification complex is specifically and timely recruited to the active promoters remains unknown. Using ER stress responsive gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 46 publications
2
94
0
1
Order By: Relevance
“…Previously, it has been reported that bZIP28 forms a transcriptional complex with NF-Y TFs, which is important for full induction of the BIP3 gene (18). Recently, bZIP28 has been shown to be involved in formation of a transcriptional complex with COMPASS-like components, which are involved in histone H3K4 trimethylation (H3K4me3), which correlates with active gene expression (33). Moreover, it is also known that histone modification plays an important role in HY5-mediated gene expression (4,34).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that bZIP28 forms a transcriptional complex with NF-Y TFs, which is important for full induction of the BIP3 gene (18). Recently, bZIP28 has been shown to be involved in formation of a transcriptional complex with COMPASS-like components, which are involved in histone H3K4 trimethylation (H3K4me3), which correlates with active gene expression (33). Moreover, it is also known that histone modification plays an important role in HY5-mediated gene expression (4,34).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, nearly all H3K4 methyl transferases characterized in Arabidopsis were those controlling H3K4me3 (Berr et al, 2015;Song et al, 2015). The only enzyme described to catalyze H3K4me2 was E, Boxplot of ChIP-seq peak height of ATX3/4/5-and SDG2-affected H3K4me3 sites.…”
Section: Atx3/4/5 Regulate H3k4 Di-and Trimethylation At a Large Numbmentioning
confidence: 99%
“…The next intriguing question raised is how such association of is fulfilled. Recently, Song et al (2015) have shown that the H3K4 methyltransferase complex can directly interact with specific transcription factor to regulate gene expression in Arabidopsis. Therefore, we speculate that ATX3/4/5 and SDG2 may interact with different transcription factors to facilitate the gene expression and generate the deposition of H3K4me3 mark at specific loci.…”
Section: Functional Redundancies Of Atx Genesmentioning
confidence: 99%
“…Interestingly, the unique AtSar1a/AtSec23a pair, but not the other Sar1 and Sec23 homologs, were recently shown to be bZIP28-dependent ER stress-responsive genes in a microarray analysis (30). bZIP28, an ER resident stress sensor/transducer related to the mammalian ATF6, is exported from the ER to the Fig.…”
Section: Er Export Of Bzip28 Is Affected By Atsar1adn Under Er Stressmentioning
confidence: 99%